Monteiro Lobato: construção ou denúncia do pensamento racista? - Formighieri, Ana Paula de Souza (2017)
In the last few years, questions have emerged related to the supposed racism expressed in letters and in the literary work by Monteiro Lobato. In this context, different groups take diverse stands on the matters of how to define and how to use Lobato's work in the classroom. Without disregarding the debate, there is the need to carry out the present research, with the intention of analysing Monteiro Lobato and his literary work within his social and historical context. His work and his way of thinking were studied in the perspective of his historical context, considering the theoretical, scientific, cultural, and legislative limitations of his time. In the same perspective, it was attempted to verify the way Lobato gives voice to his characters in his fictional works: Negrinha and O Presidente Negro. In this case, more than noting the words and individual behavior of the characters, it is also observed in which characters the demeaning adjectives are used, what their behavior is throughout the plot and what messages are expressed about the racial issue. This study starts from the assumption that analyzing terms individually does not expose the author's racism, making it necessary to understand his work within the set of social elements of his time. The research methodology used was literature review and qualitative research, considering that, as it is aimed to comprehend Lobato's work as a historical process, it becomes fundamental to carry out theoretical and legislative documents that might enlighten the context that constituted the author as a historical character. Monteiro Lobato is considered an important author to understand and reflect upon Brazilian memory, especially when it comes to culture and its influence in education. It is important to highlight that the present context demands severe opposition against racism, lest reproducing historical prejudice against the Negro. Establishing connections between the characters’ declarations and the plot’s development, as well as between Lobato’s production and his historical context it was assured not to require from the past the same kinds of consciousness, language, and approach that are from the 21st century. Thus, it is concluded that Lobato was an interlocutor of the different lines of thought expressed in the beginning of the 20th century; therefore, he cannot be considered racist or a spokesperson for racial segregation through only excerpts from his literary work, since his life and his work are important historical sources that enlighten the social and racial complexity that constitutes the Brazilian society to this day.